Microelement status changes of rats testis under increased receipts of heavy metals salts - Romanyuk A.M.; Saulyak S.V.; Moskalenko R.A.; Moskalenko Yu.V.; Budko A.Yu. (Морфологія, 2011)
The results of the study of 128 rats tissue seminal glands. We presented the experimental rats within 48 days received drinking water salts of zinc, copper, iron, manganese, chromium, and lead. The objective was to study the accumulation of zinc, copper, lead, manganese, chromium and iron in the testicular tissue in their alimentary receipt and in a correction by the drug "Tivortin." The spectrophotometry in atomic absorption mode revealed reduced levels of zinc and increased level of other studied trace elements. Accumulation of copper, iron, manganese, chromium and lead in seminal gland tissue is defined within 48 days, copper, lead and chromium exhibit the largest organ tropism.